ChemInform Abstract: Non‐enzymatic Acylative Kinetic Resolution of Primary Allylic Amines. Issue 7 (18th February 2014) - Kolleth, Amandine; Cattoen, Martin; Arseniyadis, Stellios; Cossy, Janine
Abstract A non‐enzymatic acetyl‐transfer kinetic resolution of primary amines (I), (IV), (VI), and (VIII) is reported.